Komunikasi Magis pada Fenomena Trend Live Cek Khodam: Studi Analisis Berdasarkan Hadis-hadis Tentang Perdukunan - Fadila, Lisa; Marhamah, Marhamah; Saleh, Muhammad; Wazna, Ruhama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The phenomenon of the spiritual guide check has recently widely discussed in society, especially through the TikTok platform. This practice claims that the spiritual guide residing within an individual can provide guidance, protection, or assistance to its owner. While the trend attracts public attention, it also sparks controversy regarding religious and spiritual aspects. From the Islamic perspective, practices involving occultism and magic divination with supernatural beings are prohibited, as stated in authentic hadiths. This study aims to analyze the spiritual guide check trend within the context of magical communication and its relation to Islamic teachings on sorcery as outlined in hadiths. This research used qualitative approach with library research for data collection, using Transpersonal Psychology theory by Abraham Maslow. This research finds that studying and believing in magical knowledge is forbidden and considered as an act of shirk, as it involves placing trust in beings other than Allah for protection. This study provides insights that, despite the growing popularity of the live cek khodam trend, it remains contradictory to Islamic teachings, which prohibit occultism. Therefore, education about the dangers of black magic or occultism and the importance of proper faith understanding is essential.